Post-Intoxication Inhibition of Botulinum Neurotoxin Serotype A within Neurons by Small-Molecule, Non-Peptidic Inhibitors - Ruthel, Gordon (MDPI, 2011)
Botulinum neurotoxins (BoNTs) comprise seven distinct serotypes that inhibit the release of neurotransmitter across neuromuscular junctions, resulting in potentially fatal flaccid paralysis. BoNT serotype A (BoNT/A), which targets synaptosomal-associated protein of 25kDa (SNAP-25), is particularly long-lived within neurons and requires a longer time for recovery of neuromuscular function. There are currently no treatments available to counteract BoNT/A after it has entered the neuronal cytosol. In this study, we examined the ability of small molecule non-peptidic inhibitors (SMNPIs) to prevent SNAP-25 cleavage post-intoxication of neurons. The progressive cleavage of SNAP-25 observed over 5 h following 1 h BoNT/A intoxication was prevented by addition of SMNPIs. In contrast, anti-BoNT/A neutralizing antibodies that strongly inhibited SNAP-25 cleavage when added during intoxication were completely ineffective when added post-intoxication. Although Bafilomycin A1, which blocks entry of BoNT/A into the cytosol by preventing endosomal acidification, inhibited SNAP-25 cleavage post-intoxication, the degree of inhibition was significantly reduced versus addition both during and after intoxication. Post-intoxication application of SMNPIs, on the other hand, was nearly as effective as application both during and after intoxication. Taken together, the results indicate that competitive SMNPIs of BoNT/A light chain can be effective within neurons post-intoxication.